SUPERVISI KLINIS PADA BIMBINGAN PEMBELAJARAN MIKRO DAN PPL IKIP PGRI MADIUN (PENELITIAN FUNDAMENTAL BERBASIS TINDAKAN KELAS) - V. Teguh Suharto; Elly's Mersina Mursidik; Fida Chasanatun (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
This study aims to: (1) knowing how clinical supervision conducted by the supervisor in improving the quality of micro teaching on campus; (2) knowing how clinical supervision conducted by teachers in improving the quality PPL officials at the school; (3) knowing how to create communications in a holistic relationship between the teacher tutors, lecturers, and students prospective educators in order to improve the micro and PPL learning in school; (4) determine how the shape of clinical supervision is expected to improve the quality of prospective teachers in the Teachers' Training College PGRI Madiun. This study used the descriptive qualitative method. Teachers' Training College campus research locations PGRI Madiun and PPL schools in the district of Madiun, Magetan and Madiun. The data source of this research is: (a) a resource which consists of officials from the campus and school officials; lecturers, teachers, tutors, students prospective educator, (b) the activity in the form of classroom practice, (c) records and documents in the form syllabus and RPP artificial prospective educators. Data collection techniques used: (a) in-depth interviews, (b) observation, (c) documentation. Sampling using purposive sampling, time sampling, and internal sampling. Validation data using triangulation techniques and informants review. Data analysis techniques using an interactive model. The results of the study as follows: (1) Supervision is done by the supervisor in micro teaching still various learning implementation. This is because the faculty of understanding of the basic principles of clinical supervision and technical implementation is not optimally controlled. (2) Supervision is done by the teacher in the PPL officials at the school has been good, although still need to be improved. Teacher tutors do not fully understand the concept of technical and operational how clinical supervision implemented, but they are already implementing sharing and discussions with well although still individualistic. (3) The ability of the students in the PPL and the creation of a holistic communication between teachers and tutors, lecturers, and students prospective educators in micro and PPL learning in schools needs to be improved, especially in the ability to speak, eight teaching skills, and mastery of subject material. (4) The form of supervision is expected in the future to improve the quality of learning and PPL i.e., micro supervision of academic clinics actually do the sharing, clinical discussions, providing feedback about the weakness of the practitioner that can be corrected optimally.